1972
DOI: 10.1121/1.1913050
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic Membrane Vibrations in Cats Studied by Time-Averaged Holography

Abstract: The vibratory characteristics of the cat's tympanic membrane (TM) were studied in fresh cadavers and living animals with the aid of time-averaged holography. Initially, technical difficulties were presented by the TM's small size, low stiffness, and its transparency. Time-averaged holograms of the TM were obtained for various sound-pressure levels at a number of frequencies between 600 and 6000 Hz. Reconstructions of such holograms show an image of the TM superimposed by isoamplitude contour lines giving the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1
4

Year Published

1978
1978
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(113 citation statements)
references
References 0 publications
11
97
1
4
Order By: Relevance
“…Our single model has been able to show both a smoothly varying middle-ear pressure transfer function (24) and the highly nonuniform displacement patterns seen experimentally (23,25) for frequencies up to 20 kHz. For frequencies Ͻ3 kHz, the eardrum surface moves together in unison (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Our single model has been able to show both a smoothly varying middle-ear pressure transfer function (24) and the highly nonuniform displacement patterns seen experimentally (23,25) for frequencies up to 20 kHz. For frequencies Ͻ3 kHz, the eardrum surface moves together in unison (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, this arrangement causes the outward curved shape of the tympanic membrane and provides the cante lever first proposed by Helmholtz [15,16]. It is difficult to reconstruct this sophisticated design and post operative the acoustic characteristics of tympanic membrane may change [17].…”
Section: Discussionmentioning
confidence: 99%
“…Tonndorf and Khanna (1972) and Khanna and Tonndorf (1972) were the first to study vibration patterns of the human and cat TM by time-averaged laser holography, at frequencies up to 5 and 6 kHz, respectively. They observed that, in both species, the maximum displacement happens in the posterior region, and for frequencies beyond 2.5 kHz, the simple low-frequency vibration pattern starts to break up and vibration patterns become more complex.…”
Section: Introductionmentioning
confidence: 99%